Control strategy for a non-hybrid hydrostatic transmission construction vehicle based on power follower - Yuan, Haoyu; Wang, Jixin; Du, Shaofeng; Han, Yunwu; Wang, Jindong (Transport, 2022)
To achieve energy-saving control of non-hybrid Hydrostatic Transmission Construction Vehicles (HST-CVs) with traditional closed-loop Hydrostatic Transmission (HST) for both propulsion and working systems, this paper presents a control strategy for non-hybrid HST-CVs by referring to the power follower method of the hybrid Energy Management Strategy (EMS). Through the implementation of the presented control strategy by coordinated control of the engine speed and hydraulic pump displacement, the engine can be controlled to operate at the pre-set low Brake Specific Fuel Consumption (BSFC) area, similar to that of the hybrid vehicles adopting a power follower control strategy but without the additional installation of accumulators in the hydraulic system. The effect of the control strategy is verified via experimental tests and MATLAB/SIMULINK–AMESIM COLlaborative SIMulation (COSIM). The simulation results show that the proposed control strategy can achieve the expected control target under both highway and off-road conditions.